Leachability of Metal Ions in TCLP Leachate of Solidified Petroleum Sludge - Mohd Zain, Asna (2014)
Toxicity characteristic leaching procedure was executed on solidified petroleum sludge to investigate the metal ions release in leaching medium extractant fluid number 2, U.S.EPA SW-846 TCLP. Nine metal ions from solidified sludge in ordinary Portland cement were evaluated at water to cement ratio of 0.4 to 0.5 and incorporation of 5-15% cement replacement materials. Five cement replacement materials namely, rice husk ash, condense silica fume, activated carbon, fly ash and meta kaolin were selected for solidified sludge in the cement. Solidified sludge with cement replacement materials indicates minimum leachability of metal ions.